2021
DOI: 10.3389/fphar.2021.632662
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Neuroserpin Exacerbates CoCl2 Induced Hypoxic Injury in the Zebrafish Model by Increased Oxidative Stress

Abstract: Protective strategy against hypoxic-ischemic (H/I) induced injury has been intensively discussed. Neuroserpin, an inhibitor for tissue plasminogen activator (tPA), has been proved a vital neuroprotective agent in cerebral ischemia mouse model and oxygen-glucose deprivation and reoxygenation (OGD/R) cell model. Neuroserpin is a promising therapeutic hint for neonatal hypoxic-ischemia injury. Here, we established a neuroserpin deficient zebrafish to study its role in CoCl2 chemically induced hypoxic injury. CoCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…In our experiment, we observed the location of Nrf2 protein by laser confocal microscope, and found that Nrf2 protein exists in the cytoplasm of hippocampal neuronal cells under normoxia state, while neuronal cells undergo oxidative stress under hypoxia state after CoCl2 treatment. These results were consistent with previous studies 37 . In addition, our results showed that Nrf2 protein enters the nucleus, and the level of ROS increases significantly, which is similar with some researches 38 .…”
Section: Discussionsupporting
confidence: 94%
“…In our experiment, we observed the location of Nrf2 protein by laser confocal microscope, and found that Nrf2 protein exists in the cytoplasm of hippocampal neuronal cells under normoxia state, while neuronal cells undergo oxidative stress under hypoxia state after CoCl2 treatment. These results were consistent with previous studies 37 . In addition, our results showed that Nrf2 protein enters the nucleus, and the level of ROS increases significantly, which is similar with some researches 38 .…”
Section: Discussionsupporting
confidence: 94%
“…Such phenotype was observed on knockdown of jnk2 morpholino, which resulted in 9% of the embryos displaying a complete lack of a tail. The hypoxia‐inducing effect of CoCl 2 in zebrafish is evident from several studies and results in increased expression of angiogenesis and its growth factors (Han et al, 2021; Vivek et al, 2015; Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then subcultured or inoculated into 96-well plates according to experimental design. Cobalt chloride (CoCl 2 ) is used as a common chemical hypoxic agent to simulate hypoxic/ischemic conditions in a variety of cells (Pecoraro, Pinto, & Popolo, 2018;Han, Zhang, Dong, Wang, & Wang, 2021). Based on the results of the CCK-8 assay, Nar and CoCl 2 concentrations were determined.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%